Evidence-Based Social Sciences: A New Emerging Field - Zarghi, Nazila; Soheil Dastmalchian Khorasani (European Journal of Social Science Education and Research, 2021)
Evidence based social sciences, is one of the state-of- the-art area in this field. It is making decisions on the basis of conscientious, explicit and judicious use of the best available evidence from multiple sources. It also could be conducive to evidence based social work, i.e a kind of evidence based practice in some extent. In this new emerging field, the research findings help social workers in different levels of social sciences such as policy making, management, academic area, education, and social settings, etc.When using research in real setting, it is necessary to do critical appraisal, not only for trustingon internal validity or rigor methodology of the paper, but also for knowing in what extent research findings could be applied in real setting. Undoubtedly, the latter it is a kind of subjective judgment. As social sciences findings are highly context bound, it is necessary to pay more attention to this area. The present paper tries to introduce firstly evidence based social sciences and its importance and then propose criteria for critical appraisal of research findings for application in society.